Amelogenesis imperfecta in an early 20th century population from central Portugal - Wasterlain, S. N. (2008)
This paper details the differential diagnosis of an unusual tooth morphology observed in two adult males from the identified osteological collections held at the Museum of Anthropology of the University of Coimbra, Portugal. The differential diagnosis is based on the morphological and radiographic analysis of the teeth of these individuals, and gives rise to several possible pathological conditions, namely: regurgitation erosion, mottled enamel due to fluorosis, dentinogenesis imperfecta, amelogenesis imperfecta, and osteogenesis imperfecta. Of these, amelogenesis imperfecta remains the most probable cause for one individual, and although dentinogenesis imperfecta was considered for the other based on the morphological features, the final diagnosis was changed to the former based on accurate radiological evidence. Since there are only a few reported cases of these conditions in the osteoarchaeological literature, we find it to be interesting and important to report these two cases. The scarcity of reports in the palaeopathological literature, compared with the prevalence of these tooth structure anomalies in living populations, lead us to consider amelogenesis imperfecta and dentinogenesis imperfecta to be probably misdiagnosed, and hence under-reported. Copyright © 2008 John Wiley & Sons, Ltd.